Determinants of Economic Growth in East Lombok District 2017-2021 - Titin Sri Farida Hartati; Taufiq Chaidir (Experimental Student Experiences, 2024)
The success of development is characterized by high economic growth. Economic growth is expected to increase production factors (investment and labor), which causes economic development to continue to increase. This study aims to analyze investment and labor as determinants of economic growth in East Lombok District partially and simultaneously. This research uses a quantitative approach and explanatory research type with time series data for 2017-2021 sourced from the Central Statistics Agency and the Investment Office and One-Stop Integrated Services of East Lombok Regency. The method used is the OLS (Ordinary Least Square) analysis method. The results of this study show that the investment variablehas a positive and insignificant effect on economic growth in East Lombok Regency. On the variable,work has a negative and insignificant effect on economic growth in East Lombok Regency. While the variables iinvestment and worktogether do not have a significant effect on economic growth in East Lombok Regency. The determinant coefficient has a contribution of influence contribution of 14.35 percent.